Analisis Kompetensi Nazhir terkait Penggunaan Wakaf Uang sebagai Instrumen Dana Pembangunan Infrastruktur dalam Bentuk Surat Berharga Syariah Negara: Literature Review - Muhammad Tricahyo Permadi; Ifa Hanifah Senjiati; Ira Siti Rohmah Maulida (UNISBA Press, 2022)
Abstract. Indonesia as a country with the largest Muslim population in the world, has a huge potential for waqf. This potential is supported by the increasing number of Muslim philanthropic institutions in Indonesia. progress and development of investment products are increasingly diverse. So waqf also experienced the same thing. In 2020, the Ministry of Finance of the Republic of Indonesia issued a waqf-based investment product, namely Retail CWLS, where this product is a waqf-based sukuk. On the other hand, Nazhir as the waqf manager is considered not to have the ability to manage this waqf sukuk. The objects of this research are nationally published journals accredited by Sinta, as well as published international journals indexed by Scimago. The search keywords on the Dimensions search engine are; 1. Nazhir's competence; 2. Mutawalli Waqf; 3. Waqf and Sukuk. This study aims to determine the condition of Nazhir's competence and to find out what the management of the sukuk link money waqf is like. This study is a literature review study in which data were analyzed using the Dimensions.ai application and the VOSviewer application. The indicators that must be possessed by professional nazhir are Knowledge, Education and Experience. The conclusion of this study is that the competence of nazhir related to the management of cash waqf in Indonesia is still low, so that training and certification are needed to improve the quality of nazhir's competence. Abstrak. Indonesia sebagai negara dengan populasi muslim terbesar di dunia, memiliki potensi wakaf yang sangat besar. Potensi ini didukung oleh banyaknya lembaga filantropi Muslim di Indonesia yang semakin ramai. Kemajuan dan perkembangan produk-produk investasi pun semakin beragam. Maka wakaf pun mengalami hal yang demikian. Pada tahun 2020, Kementerian Keuangan Republik Indonesia mengeluarkan produk investasi berbasis wakaf yakni CWLS Ritel, dimana produk ini adalah sukuk berbasis wakaf. Disisi lain, nazhir sebagai pengelola wakaf dinilai belum memiliki kemampuan yang mumpuni dalam mengelola sukuk wakaf ini. Adapun objek penelitian ini adalah jurnal terpublikasi nasional dan terakreditasi Sinta, serta jurnal internasional terpublikasi dan terindex Scimago. Adapun kata kunci pencarian pada mesin pencarian Dimensions adalah; 1. Kompetensi Nazhir; 2. Mutawalli Waqf; 3. Waqf and Sukuk. Penelitian ini bertujuan untuk mengetahui kondisi kompetensi Nazhir serta mengetahui seperti apa pengelolaan wakaf uang link sukuk. Penelitian ini adalah penelitian literature review yang mana data dianalisis menggunakan aplikasi Dimensions.ai dan aplikasi VOSviewer. Adapun indikator yang harus dimiliki oleh nazhir profesional adalah Pengetahuan, Pendidikan dan Pengalaman. kesimpulan dari penelitian ini adalah bahwa kompetensi nazhir terkait pengelolaan wakaf uang di Indonesia masih rendah, sehingga diperlukan adanya pelatihan dan sertifikasi yang dapat meningkatkan kualitas kompetensi nazhir.